On the use of entropy in Markovian model of rainfall - MUKHOPADHYAY, S. K. (MAUSAM, 1994)
A statistical study of the annual rainfall data at Cocch Behar district during the period t90 1 to t9S has been undertaken by using. Markov chain model. One step 3 X3 Ma rcov chain model has been used in (his study. The outcomes of the model reveal normal, bad and good year of rainfall a t the two stations of thi s district. The hypoth esis of independence has been tested on the use of entropy and it has been ver ified using likelih ood ra tio criterion. The results of the two methods are the same-tha t the yearly rainfall occurrence may be regarded as independent at the two places o f the district.